Title: Immunotherapy; a ground-breaking remedy for spinal cord injury with stumbling blocks: An overview - Saeed, Yasmeen (Frontiers in Pharmacology, 2023)
Spinal cord injury (SCI) is a debilitating disorder with no known standard and effective treatment. Despite its ability to exacerbate SCI sequel by accelerating auto-reactive immune cells, an immune response is also considered essential to the healing process. Therefore, immunotherapeutic strategies targeting spinal cord injuries may benefit from the dual nature of immune responses. An increasing body of research suggests that immunization against myelin inhibitors can promote axon remyelination after SCI. However, despite advancements in our understanding of neuroimmune responses, immunoregulation-based therapeutic strategies have yet to receive widespread acceptance. Therefore, it is a prerequisite to enhance the understanding of immune regulation to ensure the safety and efficacy of immunotherapeutic treatments. The objective of the present study was to provide an overview of previous studies regarding the advantages and limitations of immunotherapeutic strategies for functional recovery after spinal cord injury, especially in light of limiting factors related to DNA and cell-based vaccination strategies by providing a novel prospect to lay the foundation for future studies that will help devise a safe and effective treatment for spinal cord injury.